A Career as a Woman with the Canadian Hydrographic Service - Cormier, J. (The International Hydrographic Review, 2021)
This note was written in the context of the new "Empowering Women in Hydrography" initiative. It is encouraging and remarkable to see the commendable commitment of the International Hydrographic Organization (IHO) to foster and empower women in prominent and increasingly senior positions at the strategic and managerial level in IHO Member State Hydrographic Offices and within the IHO.